SISTEM KONTROL PENGHEMAT ENERGI LISTRIK BERBASIS MIKROKONTROLER ARDUINO UNO R3 - Rizal Fadilah; Garno Garno; Jajam Haerul Jaman (STKIP PGRI Situbondo, 2023)
The research is engaged in the design of an automatic room control system for saving electrical energy. A user of electrical equipment, room lighting that often neglects to turn off electricity after use, is a problem of wasting electricity use. So it needs to be done to overcome the waste of electricity for efficient use of power. Efficiency by making an Arduino-based control system with a PIR sensor as a motion detector and a relay module as an automatic switch. The results showed that the efficiency of wasting electricity was 22.65% from the comparison for 3 months of use with and without the control system.